2024
DOI: 10.1039/d3bm01783d
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous capsule-resistant, controllably degradable and functionalizable zwitterion-albumin hybrid hydrogels

Zuolong Liu,
Xianchi Zhou,
Yongcheng Chen
et al.

Abstract: We present a biocompatible, controllably degradable, and functionalizable zwitterion-albumin hybrid hydrogel with long-term resistance against foreign body responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…[80] Ultralow fouling capacity was documented for zwitterionic polymers, making them attractive candidates for use as anti-FBR materials. [81][82][83][84] Despite their potential, an early study investigating the FBR against zwitterionic materials showed unsatisfactory results. [77] In the experiment, poly(sulfobetaine methacrylate) (PSBMA), P(CBMA-co-HEMA), and PHEMA hydrogels were made using a tetra(ethylene glycol) dimethacrylate (TEGDMA) crosslinker and implanted into C57BL/6 mice.…”
Section: Zwitterionic Hydrogelsmentioning
confidence: 99%
“…[80] Ultralow fouling capacity was documented for zwitterionic polymers, making them attractive candidates for use as anti-FBR materials. [81][82][83][84] Despite their potential, an early study investigating the FBR against zwitterionic materials showed unsatisfactory results. [77] In the experiment, poly(sulfobetaine methacrylate) (PSBMA), P(CBMA-co-HEMA), and PHEMA hydrogels were made using a tetra(ethylene glycol) dimethacrylate (TEGDMA) crosslinker and implanted into C57BL/6 mice.…”
Section: Zwitterionic Hydrogelsmentioning
confidence: 99%
“…[ 4 , 5 , 6 ] However, the foreign body response (FBR) triggered by these implanted materials can lead to fibrotic encapsulation, compromising the efficacy of implants and giving rise to complications. [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ] The FBR can be elicited by a wide range of materials employed in the fabrication of biomedical devices, irrespective of whether they are composed of metals, inorganics, or natural and synthetic polymers. [ 14 , 15 , 16 , 17 ] Surprisingly, even materials conventionally known for their favorable biocompatibility, such as hydrophilic polymers like polyethylene glycol (PEG) and poly(2‐hydroxyethyl methacrylate), have been found to evoke strong FBR.…”
Section: Introductionmentioning
confidence: 99%